2021
DOI: 10.1016/j.celrep.2021.109764
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling reveals additional regulation at co-transcriptional level by post-transcriptional sRNA regulators

Abstract: Highlights d SgrS and RyhB can regulate transcripts as soon as their binding sites exit the RNAP d Co-transcriptional regulation is promoted by Rho-dependent termination d Binding to the target mRNA is the primary determinant of hierarchical regulation d Co-and post-transcriptional level regulation all contribute to overall efficiency

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Gel retardation assays showed in vitro that RsaG recognized a high number of RNAs with various binding affinities, which illustrates a possible hierarchical regulation. However, binding affinities in vivo might be different as the sRNA is expected to bind the mRNA cotranscriptionally and transacting factors might also modulate the mRNA structure and facilitate the pairings (Reyer et al, 2021). Among the target RNAs, none of them are directly linked to the G6P catabolism per se but some of them are involved in carbohydrate-dependent metabolic pathways (ccpA, ldh1) and to redox homeostasis (rex).…”
Section: Rsag Expands the Regulon Of Hptrsmentioning
confidence: 99%
“…Gel retardation assays showed in vitro that RsaG recognized a high number of RNAs with various binding affinities, which illustrates a possible hierarchical regulation. However, binding affinities in vivo might be different as the sRNA is expected to bind the mRNA cotranscriptionally and transacting factors might also modulate the mRNA structure and facilitate the pairings (Reyer et al, 2021). Among the target RNAs, none of them are directly linked to the G6P catabolism per se but some of them are involved in carbohydrate-dependent metabolic pathways (ccpA, ldh1) and to redox homeostasis (rex).…”
Section: Rsag Expands the Regulon Of Hptrsmentioning
confidence: 99%
“…Repressed translation of galK leads to increased Rho-dependent termination within galK (Wang et al , 2015). Our recent work added to these translation-dependent examples of regulation by demonstrating that sRNAs including SgrS and RyhB that were previously described as post-transcriptional regulators because of their demonstrated ability to repress translation of mRNA targets can also act on some (but not all) targets co-transcriptionally to promote Rho-dependent termination (Reyer et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While most studies performed in the last decades have led to the idea that sRNAs regulate gene expression at the post-transcriptional level ( 58–60 ), it has recently been shown that sRNAs can also operate cotranscriptionally by controlling Rho transcription termination ( 61–63 ). For ChiX, Rho transcription termination is indirectly controlled through the modulation of translation initiation in Salmonella enterica ( 64 ).…”
Section: Discussionmentioning
confidence: 99%